2021
DOI: 10.3390/covid1010002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Polyphenolic, Standardized Green Tea Extract for the Treatment of COVID-19 Syndrome: A Proof-of-Principle Study

Abstract: The lack of therapies for moderate COVID-19 syndrome prompted us to use a standardized polyphenolic green tea extract rich in catechins during the lockdown due to the pandemic in Italy (Autumn 2020). Catechins are powerful antioxidant, anti-inflammatory and antiviral agents that are safe for human use. While awaiting hospitalization, 10 swab-positive patients, symptomatic for SARS-COV-2, were treated for 15 days at home with two sessions of inhalation plus three capsules per day (total catechins: 840 mg; total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Manusco et al [123] reported that at day 10, 0.7% of the patients had a first negative swab test, with the percentage increasing to 19.0% on day 20. It seems that green tea polyphenol treatment might have helped clear the virus from the patients, as 20% of patients from the Bettuzzi et al study [117] had the first negative swab at 10 days, increasing to 70% at day 20 from the first swab. As the authors declared, the effect of green tea polyphenols was noticeable, as the probability of this happening by chance was p < 0.0023 at day 10 or p < 0.005 at day 20 (one-tailed Fisher-Yates test performed by the authors of the study), but the mechanism was unknown.…”
Section: Green Tea Polyphenols As An Addition To Standard Of Care Therapy For Covid-19mentioning
confidence: 97%
See 3 more Smart Citations
“…Manusco et al [123] reported that at day 10, 0.7% of the patients had a first negative swab test, with the percentage increasing to 19.0% on day 20. It seems that green tea polyphenol treatment might have helped clear the virus from the patients, as 20% of patients from the Bettuzzi et al study [117] had the first negative swab at 10 days, increasing to 70% at day 20 from the first swab. As the authors declared, the effect of green tea polyphenols was noticeable, as the probability of this happening by chance was p < 0.0023 at day 10 or p < 0.005 at day 20 (one-tailed Fisher-Yates test performed by the authors of the study), but the mechanism was unknown.…”
Section: Green Tea Polyphenols As An Addition To Standard Of Care Therapy For Covid-19mentioning
confidence: 97%
“…The lack of therapies for COVID-19 patients with mild and moderate symptoms compelled a group of researchers from the Istituto Nazionale Biostrutture e Biosistemi, Italy, to use standardized polyphenolic green tea extract during the lockdown in Italy in Autumn 2020 [117] to treat ten symptomatic COVID-19 patients with positive nasopharyngeal swab tests for the SARS-CoV-2 virus. The group already had experience in green tea extract application and dosage in animal [118] and clinical studies [119] related to vascular and cancer disease.…”
Section: Green Tea Polyphenols As An Addition To Standard Of Care Therapy For Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic blocking of p38 could consequently impair COVID-19 infection. Thus, they revealed a common pattern that virus-induced p38 MAPK activation facilitates viral infection, and targeting p38 MAPK is a promising antiviral strategy [252]. It is a successful example to use the knowledge of animal toxic peptide for probing and addressing some of the major health challenges of our time such as viral infection.…”
Section: Antiviral Peptides Derived From Scorpion Venomsmentioning
confidence: 99%